(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
يقدمّ البحث نتائج دراسة ومعالجة النتائج التجريبية في النظام النبضي لتبخّر قطرات المحلول المائي لكربونات البوتاسيوم K2CO3 وبنسب تركيز تتراوح ما بين (60-5)% في اللهب الهيدروكربوني. بيّنت الدراسة أنّ العملية رباعية المراحل وأن هناك تغيرات لا خطية نبضية في حجم القطرات في المرحلة الثالثة وحيث تمت مناقشة الآلية الفيزيائية لظهور النظام النبضي لتبخّر قطرات المحلول الملحي المدروس. The experimental results of studying the kinetics of evaporation of a drop of potassium carbonate water solution with a concentration from 5 up to 60% in a hydro carbonic flame are presented. It is shown that the process is of four-stages and there are nonlinear oscillations of the drop size (pulsations) at the third stage. Physical and mathematical processing of the results is carried out, allowing estimating the mechanism of the proceeding processes